PENGARUH KONSUMSI APEL (Pyrus malus) TERHADAP INDEKS DEBRIS PADA ANAK USIA 9 TAHUN DI SD KATOLIK ST. THERESIA MALALAYANG (e-GiGi, 2015)
Absract: Oral hygiene andpoor food consumption patterns can lead to dental caries. One of the contributing factors that cause dental caries is debris or remnants of food stuck in the teeth. Consumption of fresh fruit and rich in vitamins, minerals, fiber and water can launch itself to the teeth cleaning. Apples are one of the fruits that can clean teeth from leftovers. Apple has a tannin which serves to clean and freshen the mouth, thus preventing caries and gingival disease. The purpose of this study was to determine the effect of consumption of apple (Pyrus malus) against the index debris in children aged 9 years in Catholic Elementary School St. Theresia Malalayang. This study was an experimental study with quasi-experimental design to approach pre and post-test treatment. The population was all students aged 9 years old in Catholic Elementary School St. Theresia Malalayang. Sampling was done by total sampling method amounted to 46 samples. Based on the results obtained in the experimental group the average value of the difference debris index of 1.07 and in the control group the average value of the difference debris index of 0.26. Hypothesis testing using the Mann-Whitney test p = 0.000 (p